Total Quality Management and Pedagogical Thought in Islamic Higher Education: A Conceptual Analysis - Rifqi Achsanul Kholqi Alfarisi; Achmad Muhlis (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to analyse and synthesize the application of Total Quality Management (TQM) in Islamic higher education based on the thoughts of Rusdi Ahmad Thu'aimah. TQM has been widely adopted as a management approach to ensure continuous quality improvement in higher education, focusing on stakeholder satisfaction and academic service enhancement. However, the implementation of TQM often emphasizes administrative and procedural aspects, neglecting the improvement of the classroom learning process, which is central to determining graduate competencies. A qualitative approach using literature study methods was employed to explore this issue and examine Thu'aimah's ideas. The study finds that Thu'aimah’s concepts, such as clarity of learning objectives, a communicative approach, competency grading, and continuous evaluation, align with TQM principles, suggesting a potential synergy between the two. The integration of TQM with a pedagogical foundation could strengthen the quality assurance system in Islamic universities, improving both administrative and learning outcomes. The research also highlights that more focus should be placed on enhancing classroom learning processes alongside accreditation standards. Moreover, TQM’s emphasis on stakeholder satisfaction can drive institutional improvements and better graduate competencies. In conclusion, the study recommends further research into practical frameworks that integrate TQM with teaching and learning strategies to holistically improve academic quality in Islamic higher education.